Risk-Adjusting the Doughnut Hole to Improve Efficiency and Equity - Richard C. van Kleef; Wynand P. M. M. van de Ven; Rene C. J. A. van Vliet (SAGE Publishing, 2011)
An important goal of consumer cost-sharing in health insurance is to increase incentives for cost containment. A relatively new cost-sharing phenomenon is the "doughnut hole": a gap in coverage starting at a predefined level of medical expenses. An important question is where to locate the starting point to achieve the strongest incentives for cost containment. We argue that the answer depends on an individual's health status. Using data from a Dutch insurer, this paper illustrates that using a risk-adjusted starting point results in both stronger incentives for cost containment and more equity than a uniform starting point.